Navigating athlete mental health: Perspectives from performance directors within elite sport - Prior, E.; Papathomas, A.; Rhind, D. (Psychology of Sport and Exercise, 2024)
Performance directors lead high-performance programmes within elite sport and where they opt to invest resources has implications for athletes. This study explores performance directors` perspectives on mental health and illness and their experiences of managing these within elite sport. We conducted semi-structured interviews with 11 performance directors, resulting in 18 h of data. Interviews were transcribed verbatim and analysed using reflexive thematic analysis. We constructed three themes: 1) making sense of mental health: legitimacy vs. scepticism; 2) mental health as athlete responsibility; and 3) simplifying and sanitising mental health. Performance directors used physical health analogies to make sense of mental health, sometimes describing unrealistic expectations regarding mental health management. They also positioned athletes as responsible for finding solutions to their mental health concerns, at times overlooking the impact of the elite sport environment. Some performance directors shared over-simplified perceptions of mental health, often focusing on `the positive` and neglecting to talk about the more challenging aspects of mental health and illness. Educating performance directors, as well as others in leadership positions, on the complexities of mental health and illness is recommended. This should include how mental illness differs from physical illness and injury, how to respond when athletes disclose mental health concerns, and how mental illness recovery is often nonlinear and subjectively defined.